Paul and the Corinthians : studies on a community in conflict : essays in honour of of Margaret Thrall - Thrall, Margaret E.; Burke, Trevor J.; Elliott, J. K. (Novum Testamentum, Supplements, 2003)
This volume has 1 and 2 Corinthians as its main focus where the various contributors address significant aspects of text, language, background, theology and exegesis. The first part of the volume deals with the issues of textual criticism and traditions available to Paul, while the second section is interdisciplinary in nature and integrates different methodologies such as social-scientific and rhetorical criticism in order to provide new insights into the text. The third and longest section addresses the varied theological problems which the community raised with Paul, including sexual matters, the timing of the resurrection the resurrection body, authority and headship, soteriology, and the question of Paul's faithfulness and integrity. The final section concentrates on the identity of Paul's opponents, his visions and apologetics.